Between the lines of the Vienna Convention? canons and other principles of interpretation in public international law - Klingler, Joseph; Parkhomenko, Yuri; Salonidis, Constantinos (Kluwer Law International, 2019)
"This handbook analyses certain particularly recognizable canons and principles of interpretation that are not expressly codified in the Vienna Convention, but that are arguably still authorized 'between the lines'. This volume represents the first modern, freestanding analysis of such canons and principles, their utility in public international law, their role in treaty interpretation and their relationship with the Vienna Convention regime."--Provided by publisher